2019
DOI: 10.12788/jhm.3263
|View full text |Cite
|
Sign up to set email alerts
|

Community Pediatric Hospitalist Workload: Results from a National Survey

Abstract: As a newly recognized subspecialty, understanding programmatic models for pediatric hospital medicine (PHM) programs is vital to lay the groundwork for a sustainable field. Although variability has been described within university-based PHM programs, there remains no national benchmark for community-based PHM programs. In this report, we describe the workload, clinical services, employment, and perception of sustainability of 70 community-based PHM programs in 29 states through a survey of community site leade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Both university and community-based hospitalist programs report high weekend, overnight, and in-house clinical effort. 7,15 Recent studies reported that a signifi cant proportion of PHM program leaders (50% of division directors at university-affi liated programs and 37% of community program leaders) perceive their program to be unsustainable. 7,15 Among university-affi liated programs, a higher burden of weekend work as well as university employment were associated with perceived unsustainability, while no specifi c program or employer characteristic was associated with this perception in community programs.…”
Section: Clinical Work Models and Sustainabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Both university and community-based hospitalist programs report high weekend, overnight, and in-house clinical effort. 7,15 Recent studies reported that a signifi cant proportion of PHM program leaders (50% of division directors at university-affi liated programs and 37% of community program leaders) perceive their program to be unsustainable. 7,15 Among university-affi liated programs, a higher burden of weekend work as well as university employment were associated with perceived unsustainability, while no specifi c program or employer characteristic was associated with this perception in community programs.…”
Section: Clinical Work Models and Sustainabilitymentioning
confidence: 99%
“…Wide variability exists in the ways that programs address overall clinical burden, with strategies including census caps, seasonal expansion of coverage, and formal back-up systems. 7,15 Additional potential solutions may include differential weighting or fi nancial incentives for nights and weekends, support for nonclinical work, loan repayment programs, and competitive salaries. 11 In addition, structuring clinical and nonclinical roles to facilitate career development and advancement may enhance career longevity.…”
Section: Clinical Work Models and Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of the Journal of Hospital Medicine, Alvarez et al present the findings of structured interviews with 70 community PHM group leaders. 6 Each participant answered 12 questions about their group, addressing the definition of a full-time workload and hours, the design of backup systems, and the respondent's perception of the program's sustainability. The sample is robust, with the caveats that it disproportionately represents the Midwest and West (34.3% each) and more than half of the groups were employed by an academic institution.…”
mentioning
confidence: 99%